Peat soils of boreal regressive bogs in West Siberia: Problems of biological diagnostics and systematics - E. A. Shishkonakova; N. A. Avetov; T. Yu. Tolpysheva (Бюллетень Почвенного института им. В.В. Докучаева, 2016)
In this paper we consider plant (geobotanical) indicators of soils, occurring in regressive bogs in the north taiga subzone of West Siberia. The specificity of regressive bogs is the difference between current vegetation and botanical composition of the peat surface horizon, which complicates their biological diagnostics. The data on peat botanical composition, degree of decomposition and thickness are presented. Destructive oligotrophic peat soils, the allocation of which is provided in the actual Russian soil classification at the level of subtype, occur in palsa bogs under shrub-lichen vegetation. Their indicators include lichens: Cladonia stellaris, C. rangiferina, C. stygia, C. arbuscula, C. mitis, Alectoria ochroleuca, Сetraria islandica, C. laevigata, Flavocetraria cucullata, F. nivalis, Govardia nigricans. A new subtype - peat oligotrophic regressive soils - which occurs in non-freezing bog is suggested. The indicators of this soil subtype in pine-shrub-sphagnum bogs are lichens Cladonia cenotea, C. chlorophaea, C. coniocraea, C. cornuta, C. crispata, C. deformis, C. gracilis, C. fimbriata, C. mitis, C. ochrochlora, C. pleurota, C. polydactyla, C. pyxidata, C. rangiferina, C. stellaris, C. subulata, C. sulphurina and liverwort Mylia anomala . The indicators of regressive soils in bog hollows are mainly liverwort Cladopodiella fluitans , mosses Warnstorfia fluitans , W. exannulata , and lichen Cetrariella delisei .